2001
DOI: 10.1046/j.1468-3083.2001.00182.x
|View full text |Cite
|
Sign up to set email alerts
|

Superficial white onychomycosis in a 3‐year‐old human immunodeficiency virus‐infected child

Abstract: We report a case of superficial white onychomycosis associated with HIV infection in a 3-year-old girl. To our knowledge, this type of onychomycosis has not been previously reported in HIV-infected prepubertal children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
1
1

Year Published

2004
2004
2018
2018

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(39 citation statements)
references
References 10 publications
0
37
1
1
Order By: Relevance
“…Young children, however, have thin, fast-growing nails, enabling easier drug penetration (11). This makes them particularly well suited for topical monotherapy, as cure can usually be achieved more easily and faster than in adults (9,(32)(33)(34)(35)(36)(37). In addition, topical monotherapy, when appropriate, alleviates concerns regarding drug toxicity and laboratory monitoring associated with systemic therapy.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
See 2 more Smart Citations
“…Young children, however, have thin, fast-growing nails, enabling easier drug penetration (11). This makes them particularly well suited for topical monotherapy, as cure can usually be achieved more easily and faster than in adults (9,(32)(33)(34)(35)(36)(37). In addition, topical monotherapy, when appropriate, alleviates concerns regarding drug toxicity and laboratory monitoring associated with systemic therapy.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…In adults, it is applied once or twice weekly for six to 12 months (46), though it appears that cure is often achieved faster in children (35,36). Clinical trials on adults have shown good efficacy with amorolfine monotherapy, with a mycological cure rate ranging from 60-76% and complete cure rate somewhat lower, ranging from 12.7-54% (47,48).…”
Section: Amorolfinementioning
confidence: 99%
See 1 more Smart Citation
“…Diabetes, psoriasis and other diseases may also increase the risk of infection. 2,3 In those health individuals who are affected, there may be a family history of onychomycosis as our patient, which gives importance to the examination of the whole family for fungal nail infections.…”
Section: Case Of Infantile Onychomycosis Successfully Cured By 5% Amomentioning
confidence: 99%
“…In a case study, amorolfine 5% nail lacquer applied once per week in a 3-year-old HIV-infected child had a good response within 4 weeks. 42 Diabetics Diabetics who are type I or type II, with sensory neuropathy and impaired circulation of the lower extremities, have an increased risk of experiencing complications from onychomycosis. The fungal disease may result in sharp and pointed nails that can cause injury to the surrounding skin.…”
Section: Hiv Patientsmentioning
confidence: 99%